Hidden in Plain Sight: Exploring Men's Use of Complementary and Alternative Medicine. Issue 1 (March 2019) - Cant, Sarah; Watts, Peter
Despite the increased attention given to the relationship between masculinity and health, the analysis of men's use of complementary and alternative medicine (CAM) is relatively underdeveloped compared with studies of female use. Through the thematic synthesis of existing research studies, this article collates and analyzes patterns of, and motivations for, male usage of CAM. We reveal that there are significant levels of male use of CAM, which cannot be explained by recourse to general or gendered patterns of health-seeking behavior or health status. Men who use CAM tend to exhibit similar demographic characteristics to female users, but also show patterns of engagement that both reinforce and challenge hegemonic masculinity. The article suggests that there remains a need to investigate the nuances and complexities of the motivations behind male usage patterns, and interrogate how these intersect with the performance of masculine selves.